Határeset . Border-line Case - Szalay, Péter (Vészi, János, 2006)
Duration: 00:32:00 In August 1989, having lived in Weimar in the German Democratic Republic, Kurt-Werner Schulz and Gundula Schafitel and their 6-year-old son were crossing Hungary on their way to the Western world. As so many of their East German fellow compatriots, they were planning to cross the border illegally. However, they had no hope of succeeding if all three of them stayed together. The story is told in the manner of a criminal investigation, spiced with some humour.